Peningkatan Niat Beli Konsumen Melalui Pelatihan Brand Concept dan Brand Image di Pujasera Kuliner Wisma (SIG) Gresik - Wenti Krisnawati; Muhammad Rosyihuddin; Kholid Albar (Abdimas Indonesian Journal, 2025)
The growth and development of MSMEs in Indonesia in the last two years has shown very interesting changes and dynamics, which reflect changes in business patterns, existing consumer behavior and the acceleration of digitalization are very influential. Talking about MSMEs, it is close to the development of food courts in Indonesia with various types of existing categories, ranging from traditional and modern categories which are commonly called food courts. The purpose of this community service activity is to help increase purchase intention and the number of visits to the Wisma SIG Culinary Food Shop (KWSIG). In the journey of the KWSIG Food Court, there are still many things that must be completed before entering the digital world, namely how MSMEs in the Food Courts are able to prepare products with a clear and good identity or we usually call product branding. The method of implementation in this activity began with socialization and then held training with a total of 24 participants which was carried out in Gresik Regency. The result of this activity is that the tenant has a product brand that is ready to be used according to the product being sold.